The Multi-Step Differential Transform Method and Its Application to Determine the Solutions of Non-Linear Oscillators (Advances in Applied Mathematics and Mechanics, 2012)
In this paper, a reliable algorithm based on an adaptation of thestandard differential transform method is presented, which is themulti-step differential transform method (MSDTM). The solutions ofnon-linear oscillators were obtained by MSDTM. Figurative comparisonsbetween the MSDTM and the classical fourth-order Runge-Kutta method (RK4)reveal that the proposed technique is a promising tool to solve non-linearoscillators.